The effect of implant surgery experience on the learning curve of a dynamic navigation system: an in vitro study - Zonghe Xu; Lin Zhou; Ming Zheng; Yanjun Lin; Wenxiu Huang; Jiang Chen; Yan Li; Dong Wu (BMC, 2023)
Abstract Background Dynamic navigation systems have a broad application prospect in digital implanting field. This study aimed to explore and compare the dynamic navigation system learning curve of dentists with different implant surgery experience through dental models. Methods The nine participants from the same hospital were divided equally into three groups. Group 1 (G1) and Group 2 (G2) were dentists who had more than 5 years of implant surgery experience. G1 also had more than 3 years of experience with dynamic navigation, while G2 had no experience with dynamic navigation. Group 3 (G3) consisted of dentists with no implant surgery experience and no experience with dynamic navigation. Each participant sequentially placed two implants (31 and 36) on dental models according to four practice courses (1-3, 4-6, 7-9, 10-12 exercises). Each dentist completed 1-3, 4-6 exercises in one day, and then 7-9 and 10-12 exercises 7 ± 1 days later. The preparation time, surgery time and related implant accuracy were analyzed. Results Three groups placed 216 implants in four practice courses. The regressions for preparation time (F = 10.294, R2 = 0.284), coronal deviation (F = 4.117, R2 = 0.071), apical deviation (F = 13.016, R2 = 0.194) and axial deviation (F = 30.736, R2 = 0.363) were statistically significant in G2. The regressions for preparation time (F = 9.544, R2 = 0.269), surgery time (F = 45.032, R2 = 0.455), apical deviation (F = 4.295, R2 = 0.074) and axial deviation (F = 21.656, R2 = 0.286) were statistically significant in G3. Regarding preparation and surgery time, differences were found between G1 and G3, G2 and G3. Regarding implant accuracy, differences were found in the first two practice courses between G1 and G3. Conclusions The operation process of dynamic navigation system is relatively simple and easy to use. The linear regression analysis showed there is a dynamic navigation learning curve for dentists with or without implant experience and the learning curve of surgery time for dentists with implant experience fluctuates. However, dentists with implant experience learn more efficiently and have a shorter learning curve.